Yesus sebagai Model Cara Hidup Selibat - Martinus Rikiwi Setiaji (Kelompok Studi Mitra Skolastikat MSC PinelengINELENG, 2022)
This paper wants to show that celibacy is a way of life that is not contrary to human nature. Celibacy is actually a supernatural way of life which originates from God's own love and becomes a heavenly way of life. Celibacy for the sake of the kingdom of God refers directly to the commandment of Jesus not to marry for the sake of the kingdom of God. Indeed, celibacy is inseparable from the problems that follow. However, this does not mean that celibacy is an impossibility because the Catholic Church has long made it a Church law. Celibacy, which is based on gratitude that God first loved the Church, is a real sign showing that God's love for man is eternal. This paper wants to reiterate that celibacy is an anomaly that must be constantly questioned and debated.